Detection and molecular characterization of Clostridium perfringens, Paeniclostridium sordellii and Clostridium septicum from lambs and goat kids with hemorrhagic abomasitis in Turkey - Kalender, Hakan; Ongor, Hasan; Timurkaan, Necati; Karagulle, Burcu; Karabulut, Burak; Incili, Canan Akdeniz; Cetinkaya, Burhan (Bmc, 2023)
BackgroundThe pathogenic Clostridia cause neurotoxic, histotoxic and enterotoxic infections in humans and animals. Several Clostridium species have been associated with abomasitis in ruminants. The present study aimed to investigate the frequency, and the presence of virulence genes, of Clostridium perfringens, Paeniclostridium sordellii and Clostridium septicum in lambs and goat kids with hemorrhagic abomasitis.ResultsA total of 38 abomasum samples, collected from lambs and goat kids of 1 week to 1 month of age in different farms located in eastern Turkey between 2021 and 2022, were evaluated by histopathology, culture and PCR. At necropsy, the abomasum of the animals was excessively filled with caseinized content and gas, and the abomasum mucosa was hemorrhagic in varying degrees. In histopathological evaluation, acute necrotizing hemorrhagic inflammation was noted in abomasum samples. The examination of swab samples by culture and PCR revealed that C. perfringens type A was the most frequently detected species (86.84%) either alone or in combination with other Clostridium species. P. sordellii, C. perfringens type F and C. septicum were also harboured in the samples, albeit at low rates. Beta2 toxin gene (cpb2) was found in three of C. perfringens type A positive samples.ConclusionIt was suggested that vaccination of pregnant animals with toxoid vaccines would be beneficial in terms of protecting newborn animals against Clostridial infections. This study investigated the presence of clostridial toxin genes in abomasal samples for the first time in Turkey.
Keywords: Hemorrhagic abomasitis; Clostridium perfringens; Paeniclostridium sordellii; Clostridium septicum; Lambs; Kids